Penyelesaian Sengketa Konsumen melalui Badan Penyelesaian Sengketa Konsumen (BPSK) Kota Serang - Arif Rahman (Universitas Serang Raya, 2018)
Consumer Dispute Settlement Board (BPSK) , as mentioned in the Rules No. 8 Years 1999 about Consumer Protection (UUPK) which is formed by the government, is the institution that responsible for holding and resolving disputes between consumers and businesses. The basic concept of the establishment of this institution is to handle the disputes between consumers and businesses. BPSK formation is intended to overcome the vagaries of litigation that tends to have long, formal and convoluted process with the alternative dispute resolution outside the court that is based on the principle of fast, simple and low cost. This research was conducted on Consumer Dispute Settlement Board (BPSK) Kota Serang by using normative juridical approach. The author conducted a review of literature regarding consumer protection law and the settlement of consumer disputes according to consumer protection codes which were collected and classified by the record in detail, systematic and focused on literature. Furthermore, the author conducted a descriptive analysis of data, in order to obtain a complete overview of the issues regarding the settlement of consumer disputes at BPSK Kota Serang.The Results of this research conducted by the author suggest a role of BPSK Serang in solving consumer disputes according to the Law No. 8 of 1999 on Consumer Protection can be resolved in three ways, which are conciliation, mediation and arbitration on the basis of selection and consent of the parties to the dispute. Verdict forms of conciliation methods and mediation are final and binding, without having to request fiat execution to the local court, while the form of the decision taken by arbitration method has to be requested fiat execution to the local Court for the arbitration award to have the executorial power. Additionally, arbitration decision of BPSK council also still has opportunities for the objection to the District Court, counted before passing 14 (fourteen) days after the arbitration decision was notified to the parties , for the party who did not accept the decision of the BPSK’s council.